Keterlibatan Masyarakat dalam Pemberantasan Tindak Pidana Narkotika - Emhasan, Ramadhan; Sudarto, Sudarto (FOCUS, 2025)
Narcotics crimes have long been the enemy of the nation and are now increasingly alarming for Indonesia and the world. The production and distribution of narcotics have become massive, not only in big cities but also in rural areas. Perpetrators of abuse are no longer limited to adults but have spread to all levels of society, including students, entrepreneurs, officials, and children. The problem of drug abuse has drawn continuous public attention and discussion, as it threatens the nation’s future. Almost all elements of society emphasize the importance of vigilance, especially in monitoring children’s social interactions to prevent exposure to narcotics. Despite global commitments to combat narcotics crimes, illicit trafficking continues to escalate, indicating that these offenses constitute extraordinary crimes. This study examines the regulation of narcotics crimes under Law Number 35 of 2009 concerning Narcotics and the role of community involvement in eradication efforts. Using a normative juridical research method, the study finds that such crimes are regulated in Articles 111–116 in conjunction with Articles 127 and 132 of Law 35/2009. Community participation includes searching for, obtaining, and providing information on suspected narcotics crimes to law enforcement or the police. The study recommends drafting a special law to strengthen community involvement in combating narcotics crimes, incorporated into the Criminal Code, legislation, government regulations, and ministerial regulations. The government is urged to create a clear and comprehensive legal framework to ensure effective and coordinated efforts in eradicating narcotics crimes.